2011
DOI: 10.1136/bjsm.2010.082495
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, appetite and weight management: understanding the compensatory responses in eating behaviour and how they contribute to variability in exercise-induced weight loss

Abstract: Does exercise promote weight loss? One of the key problems with studies assessing the efficacy of exercise as a method of weight management and obesity is that mean data are presented, and the individual variability in response is overlooked. Recent data have highlighted the need to demonstrate and characterise the individual variability in response to exercise. Do people who exercise compensate for the increase in energy expenditure via compensatory increases in hunger and food intake? We address the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 153 publications
5
96
0
1
Order By: Relevance
“…The relationship between exercise and appetite regulation has important implications 28 regarding the role of exercise in weight management (33). In recent years, 29 advancements in scientific understanding regarding the psycho-biological regulation 30 of appetite and food intake have ignited research interest around the interaction 31 between exercise, appetite regulation and energy balance (47).…”
Section: Introduction 27mentioning
confidence: 99%
“…The relationship between exercise and appetite regulation has important implications 28 regarding the role of exercise in weight management (33). In recent years, 29 advancements in scientific understanding regarding the psycho-biological regulation 30 of appetite and food intake have ignited research interest around the interaction 31 between exercise, appetite regulation and energy balance (47).…”
Section: Introduction 27mentioning
confidence: 99%
“…EI has been shown by some studies to increase in response to increased ExEE, especially in leaner populations who have lesser fat stores at baseline. Some subjects have reported increases in appetite following an increase in ExEE (King et al, 2012;King et al, 2007a). Multiple investigators have reported that increased EI in response to increased ExEE results in partial compensation, and is likely the largest contributor to less than expected weight loss (King et al, 2007b;J.…”
Section: Mechanisms Of Compensationmentioning
confidence: 99%
“…Appetite control has been shown to be regulated by an interaction of adipose tissue with peripheral signals from intestinal peptides (i.e., insulin, ghrelin, GLP-1, CCK, PYY amylin, oxyntomodulin) [37]. Exercise has also been associated with changes in peptides affecting appetite (i.e., stimulation of energy intake) and satiety (i.e., cessation of meal consumption), as well as gastric emptying [19,31]. Accordingly, ratings of appetite and implicit wanting for foods, particularly for sweet and high-fat foods have been shown to increase in response to exercise interventions [38,39].…”
Section: Compensatory Adaptations In Response To Exercise Interventionsmentioning
confidence: 99%
“…The focus on mean outcomes in response to exercise interventions, therefore, may provide misleading results. In fact, mean results potentially mask important trends at the individual level that could provide crucial information for the role of exercise and PA in health promotion [18,19]. Therefore, a better understanding of key characteristics that affect compensatory adaptations in response to exercise is needed to maximize the health benefits on an individual level.…”
Section: Introductionmentioning
confidence: 99%